Poly(aspartic acid) hydrogels showing reversible volume change upon redox stimulus. (August 2018) - Krisch, Enikő; Gyarmati, Benjámin; Barczikai, Dóra; Lapeyre, Véronique; Szilágyi, Barnabás Áron; Ravaine, Valérie; Szilágyi, András
Graphical abstract: Highlights: Redox- and pH-responsive poly(aspartic acid) (PASP) hydrogels are synthesized in aqueous solution. The degree of swelling and the stiffness of the gels can be controlled by using reducing and oxidising media. PASP nanogels are stable in reducing media and swell similarly to their macroscopic counterparts. Drug release measurements show considerably faster drug release in reducing than in oxidising environment. Abstract: Redox and pH responsive hydrogels were synthesized, which can serve as matrices for smart drug delivery systems exploiting the redox and pH gradients in the human body. Water soluble thiolated poly(aspartic acid), a biocompatible synthetic polymer, enables us to cross-link in water with a non-cleavable cross-linker, poly(ethylene glycol) diglycidyl ether. The permanent cross-linker establishes stable polymer hydrogels regardless of the redox environment, thus the gels swell but do not dissolve upon redox stimuli. The reversible response upon redox stimulus was induced by thiol-disulphide transformation inside the hydrogel. The degree of swelling and the stiffness of the macroscopic hydrogels were controlled by their chemical composition including thiol content and cross-linking ratio as well as the redox state of the hydrogels. The degree of swelling of the hydrogels showed strong pH dependence due to the polyelectrolyte nature of the polymer network. Release of a macromolecular model drug was considerably faster in reducing than in oxidising environment, which indicates the potential use of the synthesized hydrogels as redox responsive drug delivery systems. Nanogels were prepared in water-in-oil emulsion and displayed redox-responsive properties. The hydrodynamic diameter of the nanogels strongly increased upon the cleavage of the disulphide linkages in reducing solution without the disruption of the gels.